The Digital Da'wah Strategy Amid the Flow of Hoax Information - Fitri Aulia (Journal of Scientific Studies and Multidisciplinary Research, 2024)
This study examines the application of digital da’wah strategies to counter the spread of hoax information on social media, focusing on the role of the tabayyun approach and the importance of digital literacy. In the digital era, social media serves as a significant platform for disseminating Islamic teachings while simultaneously presenting challenges due to the rapid spread of misinformation, particularly on religious matters. This research employs a library research method, analyzing secondary data from academic articles, books, and credible online sources to identify effective strategies for digital da’wah. Key findings highlight the pivotal role of social media in reaching a vast audience, underscoring the necessity of verifying information (tabayyun) and enhancing digital literacy among da’is to ensure the accurate transmission of Islamic teachings. The study also identifies challenges such as the competitive nature of the digital landscape, which requires innovative content to attract engagement, and the need for collaboration with technology platforms and digital communities to amplify the message of truth. Moreover, the findings stress the importance of integrating Islamic values with contemporary digital tools to make da’wah more relevant and impactful. The research concludes by proposing a comprehensive digital da’wah strategy that combines information verification, increased digital literacy, creative approaches, and strategic partnerships. This holistic strategy is essential for effectively addressing the spread of hoaxes and reinforcing the dissemination of authentic Islamic knowledge in the digital age